Participating in a virtual learning community - Worrell, Patricia (School of Education, UWI, St. Augustine, 2008)
Over the course of one semester, 25 students enrolled in a postgraduate course in curriculum were registered as members of a virtual classroom. A discussion board was used to promote the development of a virtual learning community, and to create a safe place and a more flexible time frame in which students enrolled in the course could explore ideas in more depth and could be more reflective about their practice than would normally be possible in the physical classroom. An exploratory case study was conducted in an attempt to understand whether and how participants in the course cultivated and supported a sense of community on the board, and to identify strategies students used on the discussion board to conduct critical exploration of major concepts encountered in the course. Ethnographic methods were used to collect data. Initial findings suggest that although participation on the discussion board helped to foster a sense of community, not all students experienced such a sense of community or benefited from the experience. However, students' interactions on the board revealed improvement in the ability of most to think critically about key concepts and about their own professional experiences
Keywords: Teacher education; Online learning; Postgraduate courses; Teaching techniques; School of Education, UWI, St. Augustine; Trinidad and Tobago